2017
DOI: 10.3390/vaccines5030018
|View full text |Cite
|
Sign up to set email alerts
|

Egg-Independent Influenza Vaccines and Vaccine Candidates

Abstract: Vaccination remains the principal way to control seasonal infections and is the most effective method of reducing influenza-associated morbidity and mortality. Since the 1940s, the main method of producing influenza vaccines has been an egg-based production process. However, in the event of a pandemic, this method has a significant limitation, as the time lag from strain isolation to final dose formulation and validation is six months. Indeed, production in eggs is a relatively slow process and production yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 31 publications
0
42
0
3
Order By: Relevance
“…Given the slow production time and limited production capacity of using embryonated hen's eggs, traditional influenza vaccine manufacturers are not equipped to respond timeously, or in sufficient volume, to a pandemic outbreak (D'Aoust et al, 2010;Quan et al, 2016). Typical egg-based production of split virion vaccines can take up to 6 months due to the limitations inherent in the production platform which can be further hampered by variable production yields (Manini et al, 2017). In contrast, Medicago Inc in the USA has reported the production of a fully formulated HA VLP vaccine within 21 days from the release of the sequence for the pandemic A/H1N1(A/California/04/09) strain (D'Aoust et al, 2010).…”
Section: Influenzamentioning
confidence: 99%
“…Given the slow production time and limited production capacity of using embryonated hen's eggs, traditional influenza vaccine manufacturers are not equipped to respond timeously, or in sufficient volume, to a pandemic outbreak (D'Aoust et al, 2010;Quan et al, 2016). Typical egg-based production of split virion vaccines can take up to 6 months due to the limitations inherent in the production platform which can be further hampered by variable production yields (Manini et al, 2017). In contrast, Medicago Inc in the USA has reported the production of a fully formulated HA VLP vaccine within 21 days from the release of the sequence for the pandemic A/H1N1(A/California/04/09) strain (D'Aoust et al, 2010).…”
Section: Influenzamentioning
confidence: 99%
“…For instance, an SRMA by Liao et al [76] found that a booster did not have any beneficial effect on the immune response in patients on hemodialysis or peritoneal dialysis or in renal transplant recipients. Moreover, the novel egg-independent technologies with several potential advantages are becoming increasingly common [77,78] and should be further investigated also from the immunogenicity point of view.…”
Section: Discussionmentioning
confidence: 99%
“… Milestones in the history of influenza vaccines [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. IIV, inactivated influenza vaccine; WHO, World Health Organization; LAIV, live attenuated influenza vaccine.…”
Section: Figurementioning
confidence: 99%